NGF-TrkA Axis Enhances PDGF-C-Mediated Angiogenesis in Osteosarcoma via miR-29b-3p Suppression: A Potential Therapeutic Strategy Using Larotrectinib - Sheng-Mou Hou; Ching-Yuan Cheng; Wei-Li Chen; En-Ming Chang; Chih-Yang Lin (Life)
Angiogenesis plays a critical role in osteosarcoma (OS) growth and metastasis. While nerve growth factor (NGF) is implicated in cancer progression, its role in OS angiogenesis remains unclear. This study explored NGF’s effects on angiogenesis and the underlying molecular mechanisms. Analysis of GEO (GSE16088) data identified five angiogenesis markers significantly upregulated in OS tissues. In vitro experiments demonstrated that NGF enhanced HUVEC tube formation by upregulating platelet-derived growth factor C (PDGF-C) expression and suppressing microRNA-29b-3p (miR-29b-3p). The results of tube formation assays confirmed that NGF stimulation significantly increased the angiogenic capacity of MG63/NGF cells compared to MG63 cells. Furthermore, larotrectinib, a TrkA inhibitor, effectively reduced the migration and invasion abilities of MG63/NGF cells in a dose-dependent manner. These findings suggest that the NGF-TrkA axis promotes PDGF-C-mediated angiogenesis by inhibiting miR-29b-3p signaling. Larotrectinib could serve as a potential therapeutic agent targeting NGF-mediated angiogenesis in OS, offering a promising avenue for treatment.